Campaign English for the military - Mellor-Clark, Simon; Altamirano, Yvonne Baker de (Student's Book 1, 2004)
Campaign 1 is the first book of the new three level series aimed at military personnel. Level 1 is for false beginner learners of english and takes them to level between 1 and 2 fo stanag 6001, roughly equivalent to the council of europe's waystage level. Campaign deals with real issues that concern servicemen and women, level 1 is aimed at junior ranks including soldiers, sailors, airmen, junior ncos and young officers.